Supportive Therapy Effect On Compliance With Pulmonary Tuberculosis In Patients Kaligondang District Purbalingga - Sugeng Riyadi; Ruti Wiyati; Welas Haryati (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2013)
Incidence of pulmonary tuberculosis in 2010 Indonesia was ranked fourth after India, China and South Africa. The spread of tuberculosis cases among others is because of treatment failure is due to medication non-compliance resulting in increased knowledge necessary to improve treatment compliance. With supportive therapy is expected to be an increase in knowledge that will enhance treatment compliance pulmonary tuberculosis that will prevent the transmission and ultimately is expected to decrease the incidence of pulmonary tuberculosis. The purpose of this study was to determine the effect of supportive therapy to obedience treatment of pulmonary tuberculosis patients. The research was conducted at the Regional District Kaligondang Purbalingga.This type of research using the quasi experiment. With a population of 27 patients with pulmonary tuberculosis in District Kaligondang. Samples were taken using a total sampling technique that all patients of pulmonary tuberculosis by 27 respondents. Data were analyzed by using paired t test.Based on the analysis of the data obtained some results as follows: (1) there was a significant increase in adherence (t = -5.790 and p = 0.001). In conclusion there is supportive therapy for pulmonary tuberculosis patient treatment compliance.